Biometric Interagency Testing & Evaluation Schema (BITES) - Lazarick, R. T. (2012 IEEE Conference on Technologies for Homeland Security (HST), 2012)
This paper addresses the concepts of reusable biometric testing in a general sense, and then describes the US Government initiative to establish a mechanism to facilitate sharing of biometric testing information both within the government and with stakeholders. The fundamental motivation for promoting reuse of biometric testing information is to achieve cost avoidance. If a well defined test has been successfully completed and documented by a trusted party, then the results of that testing should be sufficient to allow other consumers of that product to rely on that test, and thereby avoid the cost of repeating that testing. The extent of reusability depends on the type of testing being conducted. The most straightforward type of testing suited for reuse are Conformance tests, such as conformance to American National Standards Institute/National Institute of Standards and Technology (ANSI/NIST) or International Organization for Standardization (ISO) standards. These tests are typically automated and are fully repeatable. Biometric Performance testing using the Technology Testing approach, is similarly repeatable and easily reused given a fixed set of biometric samples. Biometric Performance testing using the Scenario Testing approach is quite different in that it is inherently not repeatable due to the use of human test subjects, and not easily reusable. These tests are also typically expensive. There are several notable examples of testing programs for which the results have demonstrated reusability. One of the first and most visible may be the Federal Bureau of Investigation (FBI) Appendix F Certification of fingerprint image quality supported by the FBI for procurement of livescan fingerprint devices. There are fundamental prerequisites for reusable testing. First, there is a need for agreement on the method/procedure for conducting the testing and reporting the results. Secondly, the methods must be "Open", and additionally, the product must be tested by a trusted party . In order for reusable testing to work, the participants in a test must have a willingness and the authority to share the results, and establish a common level of integration. In order for reusability to succeed, there must be a capability to disseminate the information. The United States Government (USG) has established an effort to develop a repository for biometrics test methods and successfully completed test results - "BITES" - Biometric Interagency Testing and Evaluation Schema, to promote efficient and effective reuse of biometric testing information.